Embedding Islamic Values in English Teaching and Learning at IAIN Manado - Saud, Indah Wardaty; Otoluwa, Moon Hidayati; Assifa, Khoirotun Nisa (Institut Agama Islam Negeri (IAIN) Manado, 2023)
The objective of this study was to describe the Islamic values that instilled into English teaching and learning process at IAIN Manado during the academic year 2023/2024. The research specifically focused on delineating how an English lecturer integrated Islamic values into the English teaching and learning process. Employing a descriptive study with a qualitative approach, the researchers, acting as the main instrument, aimed to ascertain facts and describe phenomena. The participants in this study comprised an English lecturer and first semester students of Islamic Education Study Program at IAIN Manado. Data collection methods included observation, interviews, and documentation. The data were analyzed through involving data reduction, data display, and drawing conclusions. The research findings unfolded as follows: firstly, the integration of Islamic values into lesson plans occurred in the sections detailing instructional objectives and instructional materials. The integration of Islamic values into material development took various forms, including 1) providing texts and exercises that mirrored Islamic values relevant to the presented topic, 2) adapting the Islamic names of individuals, locations, and events within added exercises, 3) embedding pertinent verses from Al-Quran and Al-Hadith into the main material, and 4) interweaving Islamic expressions with corresponding English expressions in the main materials. Secondly, the integration of Islamic values into English teaching-learning activities involved (1) employing code mixing and code switching between English and Islamic expressions, (2) linking the discussed topic to verses from Al-Qur'an, (3) using Islamic names for individuals. Finally, the integration of Islamic values into evaluation was accomplished through both informal and formal assessment methods.Keywords: Islamic Values, English teaching and Learning, IAIN Manado